APPLICATION OF CRYPTOGRAPHY WITH DATA ENCRYPTION STANDARD (DES) ALGORITHM IN PICTURE - Angga Aditya Permana; Desi Nurnaningsih (Jurnal Informatika, 2020)
Cryptography is the science of maintaining data confidentiality, where the original text (plaintext) is encrypted using an encryption key to be ciphertext (text that has been encrypted). In this case cryptography secures data from a third party so that the third party cannot know the original contents of the data because the one who holds the key for encryption and decryption is only the sender and receiver. There are several cryptographic methods that are commonly used, one of which is DES or Data Encryption Standard. DES is included in the key-symmetric cryptography and is classified as a block cipher type